EARLY DIAGNOSIS OF GYNECOLOGICAL DISEASES: IMPORTANCE, METHODS AND PROBLEMS (World Bulletin of Public Health, 2025)
Early diagnosis of gynecological diseases plays a crucial role in improving treatment results and reducing complications. This thesis examines the importance of early detection, different diagnostic methods, and the challenges faced in implementing effective screening programs. Particular attention is paid to diseases such as cervical cancer, endometriosis and polycystic ovary syndrome (PCOS). The study also highlights modern technological advances that can help in early diagnosis and preventive measures to improve women's health.
Keywords: Early diagnosis; gynecological diseases; screening